Setting conservation targets for managed forest landscapes - Jonsson, Bengt Gunnar; Villard, Marc-André 1963- (Cambridge University Press, 2009)
Forests host a disproportionate share of the world's biodiversity. They are increasingly being seen as a refuge for genetic diversity, native species, natural structures, and ecological processes. Yet, intensive forestry threatens their value for biodiversity. The authors present concepts, approaches and case studies illustrating how biodiversity conservation can be integrated into forest management planning. They address ecological patterns and processes taking place at the scale of landscapes, or forest mosaics. This book is intended for students and researchers in conservation biology and natural resource management, as well as forest land managers and policy makers. It presents examples from many forest regions and a variety of organisms. With contributions from researchers that are familiar with forest management and forest managers working in partnership with researchers, this book provides insight and concrete tools to help shape the future of forest landscapes worldwide.